Anticancer Molecular Mechanisms of Resveratrol - Varoni, Elena M.; Lo Faro, Alfredo Fabrizio; Sharifi-Rad, Javad; Iriti, Marcello (Frontiers in Nutrition, 2016)
Resveratrol is a pleiotropic phytochemical belonging to the stilbene family. Despite it is only significantly present in grape products, a huge amount of preclinical studies investigated its anticancer properties in a plethora of cellular and animal models. Molecular mechanisms of resveratrol involved signaling pathways related to: extracellular growth factors and receptor tyrosine kinases; formation of multiprotein complexes and cell metabolism; cell proliferation and genome instability; cytoplasmic tyrosine kinase signaling (cytokine, integrin and developmental pathways); signal transduction by the transforming growth factor-β super-family; apoptosis and inflammation; immune-surveillance and hormone signaling. Resveratrol also showed a promising role to counteract multi-drug resistance: in adjuvant therapy, associated with 5-fluoruracyl and cisplatin, resveratrol had additive and/or synergistic effects increasing the chemosensitization of cancer cells. Resveratrol, by acting on diverse mechanisms simultaneously, has been emphasized as a promising, multi-target, anticancer agent, relevant in both cancer prevention and treatment.